Utility of bronchoscopically obtained frozen cytology pellets for next-generation sequencing - Chihiro Mimura; Rei Takamiya; Shodai Fujimoto; Takafumi Fukui; Atsuhiko Yatani; Jun Yamada; Mizuki Takayasu; Naoya Takata; Hiroki Sato; Kiyoko Fukuda; Koichi Furukawa; Daisuke Hazama; et al. (BMC Cancer, 2024)
Abstract Background Next-generation sequencing (NGS) is essential for lung cancer treatment. It is important to collect sufficient tissue specimens, but sometimes we cannot obtain large enough samples for NGS analysis. We investigated the yield of NGS analysis by frozen cytology pellets using an Oncomine Comprehensive Assay or Oncomine Precision Assay. Methods We retrospectively enrolled patients with lung cancer who underwent bronchoscopy at Kobe University Hospital and were enrolled in the Lung Cancer Genomic Screening Project for Individualized Medicine. We investigated the amount of extracted DNA and RNA and determined the NGS success rates. We also compared the amount of DNA and RNA by bronchoscopy methods. To create the frozen cytology pellets, we first effectively collected the cells and then quickly centrifuged and cryopreserved them. Results A total of 132 patients were enrolled in this study between May 2016 and December 2022; of them, 75 were subjected to frozen cytology pellet examinations and 57 were subjected to frozen tissue examinations. The amount of DNA and RNA obtained by frozen cytology pellets was nearly equivalent to frozen tissues. Frozen cytology pellets collected by endobronchial ultrasound-guided transbronchial needle aspiration yielded significantly more DNA than those collected by transbronchial biopsy methods. (P < 0.01) In RNA content, cytology pellets were not inferior to frozen tissue. The success rate of NGS analysis with frozen cytology pellet specimens was comparable to the success rate of NGS analysis with frozen tissue specimens. Conclusions Our study showed that frozen cytology pellets may have equivalent diagnostic value to frozen tissue for NGS analyses. Bronchial cytology specimens are usually used only for cytology, but NGS analysis is possible if enough cells are collected to create pellet specimens. In particular, the frozen cytology pellets obtained by endobronchial ultrasound-guided transbronchial needle aspiration yielded sufficient amounts of DNA. Trial registration This was registered with the University Medical Hospital Information Network in Japan (UMINCTR registration no. UMIN000052050).